2023
DOI: 10.1101/2023.02.17.528976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AC. elegansmale pheromone feminizes germline gene expression in hermaphrodites and imposes life-history costs

Abstract: Sex pheromones improve reproductive success, but also impose costs. Here we show that even brief exposure to physiological amounts of the dominantC. elegansmale pheromone, ascr#10, alters the expression of thousands of genes in hermaphrodites. The most dramatic effect on the transcriptome was the upregulation of genes expressed during oogenesis and downregulation of genes associated with male gametogenesis. Among the detrimental effects of ascr#10 on hermaphrodites is the increased risk of persistent infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This organization of the circuit limits ascr#10 responses -germline proliferation and behavioral -to actively reproducing animals. ascr#10 promotes egg laying and mating receptivity (Aprison et al, 2022b;Aprison and Ruvinsky, 2019a) as well as reduces exploration (Aprison and Ruvinsky, 2019a) and increases pharyngeal pumping (Angeles-Albores et al, 2023). The coupling between reproductive and food seeking behaviors likely assures that sufficient resources are consumed to match the increased reproductive output.…”
Section: Egg Laying Licenses Daf-7 and Lag-2 Responses To Ascr#10mentioning
confidence: 99%
“…This organization of the circuit limits ascr#10 responses -germline proliferation and behavioral -to actively reproducing animals. ascr#10 promotes egg laying and mating receptivity (Aprison et al, 2022b;Aprison and Ruvinsky, 2019a) as well as reduces exploration (Aprison and Ruvinsky, 2019a) and increases pharyngeal pumping (Angeles-Albores et al, 2023). The coupling between reproductive and food seeking behaviors likely assures that sufficient resources are consumed to match the increased reproductive output.…”
Section: Egg Laying Licenses Daf-7 and Lag-2 Responses To Ascr#10mentioning
confidence: 99%
“…27 To ask whether mating status is incorporated into mate-choice decisions, we let males choose between young adult hermaphrodites that had been co-cultured for 16 hours with young adult him-5 males or instead with sterile unc-54; him-5 males, allowing us to control for exposure to male pheromones, which can dramatically alter hermaphrodite physiology. 65,66 Males displayed a clear preference for virgin over mated hermaphrodites, indicating that they can robustly detect this quality and integrate it into their behavior (Figure 5C). Because previous work has suggested or indicated that fertility status can alter VSP production, 27,30,34 we asked whether the VSP receptor srd-1 29 was necessary for this preference.…”
Section: Multiple Cues Allow Males To Detect the Mating History Of Po...mentioning
confidence: 99%